MEMAHAMI KESETARAAN GENDER DALAM FIQH: Analisis Teori Evolusi Kontinuitas Fiqh - Hulwati Hulwati (Kafa`ah: Journal of Gender Studies, 2015)
Gender equality in Islam has orientation on righteous that is part of liberal thought meanwhile there is an opposition from some Muslim that the concept of gender equality is unacceptable one. The presence of Islam which was brought by Muhammad the messenger was to elevate woman position in society. While observing some fiqh books, it is found that the books have masculine nuance and have more alignments on man side. In particular, it is not found any chapters that discuss about woman. That is an interesting commentary on gender bias in fiqh discourse. In order to avoid an historical dichotomy that leads suspicion on fiqh that deals with gender bias, this article tries to discuss how to understand gender equality according to Islamic law (Analysis of Fiqh Continuity Evolution Theory).